A Bibliometric Mapping on Maqasid Shariah in Waqf Implementation - Hija, Liya Nabilatul (Journal of Islamic Economics Literatures, 2023)
This research aims to to determine the amount of literature on maqasid sharia and waqf and how much of it has been published in journals with the subject "Maqasid Sharia in waqf implementation." Several scientific journals are the sources of data for this study. Utilizing search terms to locate articles in the Dimensions database that contain the term "Maqasid Waqf". There are 74 journal articles have been published which is relevant to the subject. Trends in the creation of publications were utilized to Examine data pertaining to the topic of the study using the bibliometric-displaying VOSviewer software by employing the meta-analysis method. There are numerous terms that are categorized into four groups. The first cluster contains twenty-five words that fall under the heading " Maqasid Sharia Value in Islamic Social Finance and SDG". Twenty-three words are grouped under the theme " Islamic law and Waqf Development" in the second cluster. Twelve terms in the third cluster pertain to the subject of "The Impact of Waqf to Sustainable Development”. The fourth cluster, has nine members of terms associated with the subject of " Economic Development and Muslim Empowerment".